THE SMES’ JOURNEY TO INDUSTRY 4.0: A CALL FOR MORE IS STUDIES - Rostand AFFOGBOLO,; Vincent DUTOT, (Systèmes d'information et management, 2023)
Industry 4.0 (I4.0), which contributes to the current rapid pace of digitalization, is one of the hottest topics in both academia and industry. Governments and policymakers are putting in place, plans, roadmaps, and incentives at the national or regional level to promote its adoption. In Europe, for example, at least 25 country-specific plans have been attempted (Teixeira & Tavares-Lehmann, 2022). In line with this public support, organizations are also increasing their I4.0 investments. By 2022, the global I4.0 market is estimated to be worth USD 130,9 billion (Fortune Business Insights, 2022). Such a significant interest from practitioners and policymakers has led to increased attention from academics, who have published thousands of related studies. At the time of writing, a search in the Scopus database using the keywords “Industry 4.0” or “Fourth Industrial Revolution” yielded more than 29,900 papers. However, very few of these papers were published in the field of Information Systems (IS). For example, a recent Melville et al. (2023) review identified only 70 papers published in reputable IS journals and conferences. The limited number of studies on this digital phenomenon in the IS field roughly suggests our less interest as a field, leading to underdeveloped IS perspectives on I4.0 (Huber et al., 2022, p.2). However, as a sociotechnical field (Melville et al., 2023; Sarker et al., 2019), the IS discipline is in a privileged position to contribute meaningfully to the understanding of the I4.0 phenomenon (Baiyere et al., 2020, 2023), to provide insights on its impact on organizations and society, and to explain how organizations can leverage this growing digital trend to create, deliver, and capture more value than before...